Pattern synthesis considering mutual coupling for peak sidelobe suppression and null controlling via element rotation and phase optimization. Issue 1 (2nd January 2022) - Gao, Renjing; Tang, Yi; Wang, Qi; Liu, Shutian
ABSTRACT: An optimization method of pattern synthesis is proposed for peak sidelobe level (PSLL) suppression and null controlling via element rotation and phase optimization. The purpose of this method is to introduce the rotation angle of element into the anti-interference array design to further improve the radiation performance. The design objective is to suppress the PSLL while maximizing the main-beam gain with the constraint of null depth. To save the computational costs and avoid the re-mesh, the improved MoM is presented to solve the radiation problem of anti-interference array, which can accurately give the radiation field and precisely predict the null position. The sensitivity and MMA based solving procedures of the optimization problem are presented. Typical examples are provided to verify the effectiveness of the proposed method. The results show that, through collaboratively optimizing the rotation angles and excitation phases, the PSLL of anti-interference array with desired nulls is effectively suppressed.